The Implementation of the Juz 'Amma Extracurricular Program as an Effort to Develop Religious Character and Strengthen PAI Values of Zainul Hasan I Genggong Elementary School Students - Mohammad Hasan Khoirul Anwar; Ainur Rofiq Sofa (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study analyzes the implementation of the Juz 'Amma extracurricular program as an effort to foster religious character and strengthen the values of Islamic Religious Education (PAI) at Zainul Hasan I Genggong Elementary School. The research employs a descriptive qualitative approach using observation, interviews, and documentation. Informants include the principal, five Juz 'Amma instructors, and 20 fifth-grade students. The findings show that the Juz 'Amma program is carried out twice a week through the stages of tahsin, tahfidz, muroja'ah, and understanding the meanings of Qur'anic verses. Learning is conducted individually and in groups, accompanied by habituation of Islamic behavior. The program has been proven to improve students' reading and memorization of the Qur'an while instilling religious values such as discipline, responsibility, patience, and love for the Qur'an. Positive changes are evident in worship discipline, politeness, social awareness, and the ability of some students to lead prayer dhuha. These findings reinforce Thomas Lickona's character education theory and Al-Ghazali's concept of riyadhah al-nafs, and demonstrate that the Juz 'Amma program is effective as a Qur'an-based character education model in elementary schools.